Effects of grazing, phosphorus and light on the growth rates of major bacterioplankton taxa in the coastal NW Mediterranean. Issue 3 (4th May 2017) - Sánchez, Olga; Koblížek, Michal; Gasol, Josep M.; Ferrera, Isabel
Summary: Estimation of growth rates is crucial to understand the ecological role of prokaryotes and their contribution to marine biogeochemical cycling. However, there are only a few estimates for individual taxa. Two top‐down (grazing) and bottom‐up (phosphorus (P) availability) manipulation experiments were conducted under different light regimes in the NW Mediterranean Sea. Growth rate of different phylogenetic groups, including the Bacteroidetes, Rhodobacteraceae, SAR11, Gammaproteobacteria and its subgroups Alteromonadaceae and the NOR5/OM60 clade, were estimated from changes in cell numbers. Maximal growth rates were achieved in the P‐amended treatments but when comparing values between treatments (response ratios), the response to predation removal was in general larger than to P‐amendment. The Alteromonadaceae displayed the highest rates in both experiments followed by the Rhodobacteraceae, but all groups largely responded to filtration and P‐amendment, even the SAR11 which presented low growth rates. Comparing light and dark treatments, growth rates were on average equal or higher in the dark than in the light for all groups, except for the Rhodobacteraceae and particularly the NOR5 clade, groups that contain photoheterotrophic species. These results are useful to evaluate the potential contributions of different bacterial types to biogeochemical processes under changing environmental conditions.